Immune responses of dendritic cells combined with tumor-derived autophagosome vaccine on hepatocellular carcinoma - Yi, Yongxiang; Han, Jianbo; Zhao, Liang; Wang, Chunying; Fang, Yuan; Wei, Qiang; Hu, Liang; Liu, Junmao; Zhang, Yufeng; Wang, Lili (Chinese Journal of Cancer Research; Vol 27, No 6 (December 22, 2015): Chinese Journal of Cancer Research, 2015)
Background: To induce and collect tumor-derived autophagosomes (DRibbles) from tumor cells as an antitumor vaccine by inhibiting the functions of proteasomes and lysosomes. Methods: Dendritic cells (DCs) generated from peripheral blood mononuclear cell (PBMC) of hepatocellular carcinoma (HCC) patients were cocultured with DRibbles, and then surface molecules of DCs, as well as surface molecules on DCs, were determined by flow cytometry. Meanwhile, immune responses of the DCs-DRibbles were examined by mixed lymphocyte reactions. Results: DRibbles significantly induced the expression of CD80, CD83, CD86 and HLA-DR on DCs. The enzyme-linked immunosorbnent assay (ELISA) showed that IFN-γ levels after vaccination increased than before in most patients, but CD8+ proportion of PBMC increased only in nine patients. Higher levels of IFN-γ were detected in the CD8+ cells than CD4+ T cells. These results suggested that DCs-DRibbles vaccine could induce antigen-specific cellular immune response on HCC and could prime strong CD8+ T cell responses, supporting it as a tumor vaccine candidate. Conclusions: Our results demonstrate that HCC/DRibbles-pulsed DCs immunotherapy might be deployed as an effective antitumor vaccine for HCC immunotherapy in clinical trials.